(untitled) (Journal of Rangpur Medical College, 2024)
Background: Asthma-COPD overlap is a new phenotype in respiratory ailments. It has been shown that this group of patients might possess vitamin D3 deficiency. The association of vitamin D receptor (VDR) gene polymorphism with serum vitamin D status in ACO patients has not been investigated yet. Objective: To assess the association of VDR gene polymorphism (FokI) with serum vitamin D status in patients with Asthma-COPD overlap. Methods: This cross-sectional study was carried out in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2018 to July 2018 on 23 (twenty-three) patients (aged ≥40 years) with ACO. For comparison, 24 (twenty-four) apparently healthy age, smoking duration and BMI matched subjects were selected. For all participants single nucleotide polymorphism of VDR gene FokI (rs10735810) was done by DNA extraction, polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). Vitamin D3 was measured by using automated analyzer: ARCHITECT Plus ci4100. The results were expressed as mean with standard error (mean±SEM) and frequency distribution. The data were statistically analyzed by Graphpad prism (Version 7) using independent sample ‘t’ test, two sample proportion test, Fisher exact test and ANOVA test. In the interpretation of results, ≤0.05 level of probability (p) was accepted as significant. Results: The mean±SEM of serum 25(OH)D were 16.37±0.78 and 18.46±1.01 ng/ml in control and study groups, respectively. The frequency distribution of FokI genotype was 86.95% (FF), 8.69% (Ff), 4.35% (ff) and 91.66% (FF), 4.17% (Ff), 4.17% (ff) in ACO patients and healthy subjects, respectively. When FoKI VDR SNP was analyzed with serum vitamin D status in patients with ACO, statistically no association was seen. Conclusions: FokI VDR SNP is not associated with serum vitamin D status in patients with ACO. J Rang Med Col. March 2024; Vol. 9, No. 1: 22-27